The fantasy of family nineteenth-century children's literature and the myth of the domestic ideal - Thiel, Elizabeth; T&F eBooks (New York : Routledge, 2008)
The myth of the Victorian family remains a pervasive influence within a contemporary Britain that perceives itself to be in social crisis. Nostalgic for a golden age of Victorian values in which visions of supportive, united families predominate, the common consciousness, exhorted by social and political discourse, continues to vaunt the traditional, natural family as the template by which all other family forms are gauged. Yet this fantasy of family, nurtured and augmented throughout the Victorian era, was essentially a construct that belied the realities of a nineteenth-century world in which orphanhood, fostering and stepfamilies were endemic.
ch. 1. Redefining the past -- ch. 2. Snatched from "the seed-plot" of degeneracy : the "rescue" of the destitute child in tales of street-arab life -- ch. 3. Forever cursed : stepmothers, "otherness," and the reinscription of myth in transnormative family narratives -- ch. 4. "Uncles are one thing ... [but] aunts are always nasty!" : relational failures and the discourse of gender bias in foster family stories -- ch. 5. Mother, ally, friend, or foe? : the "dependable" female author as one of the family.
Includes bibliographical references (p. 187-192) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Families in literature; Children's stories, English -- History and criticism; English fiction -- 19th century -- History and criticism; Home in literature; Domestic relations in literature; Social problems in literature; Values in literature; Idealism in literature; Literature and society -- Great Britain -- History -- 19th century; Electronic books